2020
DOI: 10.37660/aspagr.2020.19.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Winter Oilseed Rape Yield Depending on Foliar Fertilization

Abstract: Background. An insufficient amount of nutrients in plants results in the disturbance of basic physiological processes, weakens the growth and development of plants, and consequently contributes to a reduction in yield. The aim of this study was to determine the effect of foliar fertilizers containing sulphur, boron and amino acids on the seed yield of three winter oilseed rape morphotypes (Monolit, PX115, PT248).Material and methods. The study was carried out in 2016-2019 at the Zawady Agricultural Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…Similar conclusions were reached by Matysiak and Miziniak [ 17 ], who showed that winter rape plants after application of the mixture of Kelpak and Lithovit in the BBCH 32 phase, and twice Lithovit (BBCH 32 and 67) were characterized by an average height of 10–11% higher compared to control plants. Similar results were obtained by Sikorska et al [ 15 ] and Przybysz et al [ 18 ], after using the Asahi SL biostimulant. Sikorska et al [ 16 ] after applying amino acids, sulphur and boron, noted a significant increase in plant height before harvest from 2.3 to 5.5 cm, but the differences between the variants were statistically insignificant.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Similar conclusions were reached by Matysiak and Miziniak [ 17 ], who showed that winter rape plants after application of the mixture of Kelpak and Lithovit in the BBCH 32 phase, and twice Lithovit (BBCH 32 and 67) were characterized by an average height of 10–11% higher compared to control plants. Similar results were obtained by Sikorska et al [ 15 ] and Przybysz et al [ 18 ], after using the Asahi SL biostimulant. Sikorska et al [ 16 ] after applying amino acids, sulphur and boron, noted a significant increase in plant height before harvest from 2.3 to 5.5 cm, but the differences between the variants were statistically insignificant.…”
Section: Resultssupporting
confidence: 90%
“…This value was higher by 13.7 cm on average compared to the long-stemmed hybrid (Tables 6 and 7 ). However, other authors [ 15 , 16 ] obtained the same height in a restored hybrid with a traditional growth type and population variety. The types of preparation used significantly increased the value of this feature compared to the control variant (Tables 6 and 7 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The highest straw yield, on average, 5.79 Mg•ha -1 was obtained in the population cultivar, and the lowest, on average 5.29 Mg•ha -1 in the semi-dwarf hybrid (Table 5). It is consistent with the results of Sikorska et al (2020). The authors also obtained the highest straw yield in the population variety Monolit, and significantly the lowest, on average, by 0.38 Mg•ha -1 in the semidwarf hybrid PX114.…”
Section: Resultssupporting
confidence: 89%
“…The starch content after outdoor drying (7.34 ± 0.14% dry matter) is 13.4% higher compared to the starch content obtained in the active ventilation dryer (6.36 ± 0.42% dry matter). In comparison with the studies of other researchers, it was observed that the corncob starch content was only 0.67% ± 0.12% dry matter according to the study by Pointner et al [51], while the variation in maize cob dry matter content ranged from 455 to 524 g according to the study by Szyszkowska et al [52]. Kaliyan and Morey [25] reported the effect of adding raw or pregelatinized starch on the strength and durability of the pellets.…”
Section: Discussionmentioning
confidence: 77%